Do necklace‐style radiotransmitters influence flushing behavior of greater sage‐grouse?. (7th January 2014) - Frye, Graham G.; Connelly, John W.; Musil, David D.; Berkley, Regan; Kemner, Michelle Commons; Cardinal, Casey; Cross, Lisa; Forbey, Jennifer S.
ABSTRACT Necklace‐style radiotransmitters are widely used in galliform research and management, but their influence on galliform flushing behavior has not been evaluated. We evaluated the hypothesis that greater sage‐grouse (Centrocercus urophasianus) with necklace‐style radiotransmitters are more likely to flush later within flocks than are their non‐collared flock mates, potentially leaving them more vulnerable to predation. During the winters of 2010–2011 and 2011–2012, we flushed 59 sage‐grouse flocks containing radiocollared individuals at 5 study areas in southern Idaho. We assessed 1) whether radiocollared birds were more likely to be the last individuals to flush within flocks, and 2) whether they flushed later than the majority of flockmates more often than expected from a random process. Additionally, we quantified the occurrence of a slapping noise that was apparently produced by contact between wings and transmitter antennas in flight. Sage‐grouse with radiocollars flushed last during 23% of flush events, which was only slightly less likely than the most likely outcome (20% of flush events). Radiocollared sage‐grouse flushed in the last half of flocks during 50% of flush events, which was the most likely outcome given a random process. We detected the wing‐slapping noise during 74% of flush events, excluding instances in which ambient noise precluded detection. Our results are not consistent with the hypothesis that sage‐grouse outfitted with necklace‐style radiocollars tend to flush later than non‐collared flock mates, but these results should be replicated with independent data before they are considered conclusive. Our observations of the wing‐slapping noise warrant further investigation to ensure that transmitters do not produce other biases in research and management efforts. © 2014 The Wildlife Society.